Autoantibodies - Shoenfeld, Yehuda, 1948-; Meroni, Pier-Luigi; Gershwin, M. Eric, 1946- (Elsevier, 2007)
Autoimmune diseases are characterized by the occurrence of antibodies reacting with self constituents of the body. This exciting new reference is an exhaustive review of the main autoantibodies identified up to now, with particular emphasis on those autoantibodies that display a clinical value. Each chapter is focused on a single family of autoantibodies by reviewing their historical notes, definition, origin and source(s) of the antigen(s) recognized, genetic associations, pathogenic mechanisms that are mediated, method(s) of detection and clinical utility (disease prevalence/association, diagnostic value, sensitivity and specificity, prognostic value). An ideal reference for anyone involved in the field of autoimmune diseases. Includes and exhaustive list of autoantibodies not covered by other publications * Short reviews can easily be checked for quick reference information * Both basic and clinical aspects are covered.